Channeling Power Across Ecological Systems: Social Regularities in Community Organizing. Issue 3 (8th January 2014) - Christens, Brian D.; Inzeo, Paula Tran; Faust, Victoria
Abstract: Relational and social network perspectives provide opportunities for more holistic conceptualizations of phenomena of interest in community psychology, including power and empowerment. In this article, we apply these tools to build on multilevel frameworks of empowerment by proposing that networks of relationships between individuals constitute the connective spaces between ecological systems. Drawing on an example of a model for grassroots community organizing practiced by WISDOM—a statewide federation supporting local community organizing initiatives in Wisconsin—we identify social regularities (i.e., relational and temporal patterns) that promote empowerment and the development and exercise of social power through building and altering relational ties. Through an emphasis on listening‐focused one‐to‐one meetings, reflection, and social analysis, WISDOM organizing initiatives construct and reinforce social regularities that develop social power in the organizing initiatives and advance psychological empowerment among participant leaders in organizing. These patterns are established by organizationally driven brokerage and mobilization of interpersonal ties, some of which span ecological systems. Hence, elements of these power‐focused social regularities can be conceptualized as cross‐system channels through which micro‐level empowerment processes feed into macro‐level exercise of social recommendations for theory and designpower, and vice versa. We describe examples of these channels in action, and offer of future action research.